Improved Stabilities of Immobilized Glucoamylase on Functionalized Mesoporous Silica Synthesised using Decane as Swelling Agent - Reni George; Sanjay Gopinath; Sankaran Sugunan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Ordered mesoporous silica, with high porosity was used to immobilize glucoamylase via adsorption and covalent binding. Immobilization of glucoamylase within mesoporous silica was successfully achieved, resulting in catalytically high efficiency during starch hydrolysis. In this study, mesoporous silica was functionalized by co-condensation of tetraethoxysilane (TEOS) with organosilane (3-aminopropyl) triethoxysilane (APTES) in a wide range of molar ratios of APTES: TEOS in the presence of triblock copolymer P123 under acidic hydrothermal conditions. The prepared materials were characterized by Small angle XRD, Nitrogen adsorption – desorption and 29Si MAS solid state NMR. N2 desorption studies showed that pore size distribution decreases due to pore blockage after functionalization and enzyme immobilization. Small angle XRD and 29Si MAS NMR study reveals mesophase formation and Si environment of the materials. The main aim of our work was to study the catalytical activity, effect of pH, temperature storage stability and reusability of covalently bound glucoamylase on mesoporous silica support. The result shows that the stability of enzyme can be enhanced by immobilization. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)